Profundo carmesí : Deep crimson - Ripstein, Arturo; Garciadiego, Paz Alicia, 1949-; Necoechea, Miguel; Barbachano, Pablo; Giménez Cacho, Daniel; Orozco, Regina; Paredes, Marisa, 1946-; Merchant, Veronica; Egurrola, Julieta (Home Vision Entertainment, 2005)
Based on the true story of the Lonely Hearts Murders, Nicolas and Coral roam the back roads of Mexico looking for lonely women who Nicolas seduces and the insanely jealous Coral then murders.